DETERMINATION OF THE CHLORINATED PESTICIDES RESIDUES IN SOILS TREATED WITH MODERN PESTICIDES - PĂNESCU, Vlad; POP, Sorin; ANTON, Mircea; BELDEAN-GALEA, Mihail Simion (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
The potential for pesticide soil contamination is a worldwide concern, due to the intensive use of organochlorine compounds. The use of pesticides has offered significant economic benefits by increasing the production of food and preventing different form of diseases, therefore their use has affected not only the health of human population, but the environment as well. Organochlorine pesticides like Aldrin, Chlordane, DDT, Dieldrin, Endrin and Heptachlor have been banned after the 2001 Stockholm convention. That is why many jurisdictions try to control human exposure by specifying the soil’s maximum allowable concentration. 12 soil samples were collected from different parts of Romania, aiming to evaluate the organochlorine concentration in order to study if the soils have been treated with this type of pesticides. Each sample was dried, extracted with hexane by ultrasonication and analyzed by GC-ECD. The results of the analyzed samples showed low concentrations, ranging between 28.36 and 73.19 μg/kg. The most identified compounds were Alpha HCH, Beta HCH, Heptachlor, Aldrin, Heptaclhor epoxide, trans-Clordane, Endosulfan I, 4,4` DDE and Dieldrin+Endrin.